Fabrication of electrospun antibacterial PVA/Cs nanofibers loaded with CuNPs and AgNPs by an in-situ method. (December 2018) - Kharaghani, Davood; Khan, Muhammad Qamar; Tamada, Yasushi; Ogasawara, Hiroshi; Inoue, Yuma; Saito, Yusuke; Hashmi, Motahira; Kim, Ick Soo
Abstract: Scientific efforts have been made to study and develop the efficient product to be used beyond conventional antibiotic treatments against bacteria and funguses mainly in the wound dressing. Therefore, in this innovative study, the authors investigated the development of hybrid nanofibers of chitosan/polyvinyl alcohol/nano-hydroxyapatite with the composition of copper nanoparticles for wound dressing potential. Therefore, copper/silver with ratio 1:1, copper nanoparticles and silver nanoparticles were chosen as variable to comparison the biocompatibility and antibacterial properties between copper and silver nanoparticles. The nanoparticle loaded to nanofibers by the in-situ method to prepare the chemical bonding between nanofibers and nanoparticles. All characterization results were appreciable for successful synthesis of nano-hydroxyapatite in the nanofibers matrix and loading metallic nanoparticles with chemical reactions between nanoparticles and nanofibers, due to OH deformation of Cs/PVA/nHA nanofibers and reaction with nano-particles. Although the in-vitro results showed PVA/Cs nanofibers loaded with Cu/Ag nanoparticles, is the most appropriate sample for wound dressings because it has very good inhibition zone against the gram negative and gram positive bacteria. This composite also has the good biocompatibility and no toxicity which is good sign for cell attachment and biocompatibility. Highlights: The PVA/Cs hybrid nanofibers successfully prepared by electrospinning. The nHA and metallic nanoparticles loaded into nanofibers. Antibacterial test showed appropriate properties for all samples. The toxicity did not observe in CuNPs loaded nanofibers. AgNPs/CuNPs loaded nanofibers suggested as the potential nanofiber wound dressing.